Analysis of used frying oils. Issue 7 (10th July 2013) - Dobarganes, Carmen; Márquez‐Ruiz, Gloria
Abstract The analysis of used frying oils to ensure quality of fried foods has become a subject of great concern for health administrations, food processors and consumers, especially since some compounds formed at high temperatures impair the nutritional value of fats and have adverse health effects. At present, three lines of research on the analysis of frying oils stand out: first, development of techniques for the quantitative analysis of the new compounds formed; second, the evaluation of useful rapid methods to be applied in situ for monitoring oil quality in fried food outlets; and third, the application of the most advanced analytical techniques to delve into the structure of individual oxidized compounds present in fried foods.